Differentially fed compact dual-band implantable antenna for biotelemetry - Liu, Y.; Chen, Y.; Juwono, Filbert Hilman (2016)
© 2016 IEEE. A novel differentially fed dual-band planar antenna operating at the medical implant communication service (MICS) band (402-405 MHz) and the industrial, scientific and medical (ISM) bands (2400-2480 MHz) is presented. The measured 10-dB differential reflection coefficient bandwidth is 389-419 MHz (7.4%) at the lower band and 2395-2563 MHz (6.6%) at the upper band, respectively. The volume of the implantable antenna is only 642.62 mm3 (22mm×23mm×1.27mm).